Estudo petrográfico das rochas hospedeiras e de isótopos de chumbo do minério aurífero do alvo Pau da Merenda, campo mineralizado do Cuiú-Cuiú, Província Aurífera do Tapajós, Estado do Pará - SILVA JUNIOR, Carlos Alberto dos Santos (2020)
The Tapajós Gold Province (TGP) is located in the central-south portion of the Amazonian Craton and is a major metallogenic province in Brazil. The Cuiú-Cuiú goldfield is located approximately in the central sector of this province. The goldfield is composed of several showings, prospects and deposits (Central, Raimundinha, Pau da Merenda, Guarim, Jerimum de Cima, Jerimum de Baixo, Nhô, Moreira Gomes, Babi, and others of minor importance). The goals of this study were to define the sulfide mineralogy associated with gold mineralization, their textural relationships, the age of the ore-forming event and the source of Pb present in the sulfide minerals of the Pau da Merenda target. The host rocks in this target were classified as brecciated and hydrothermally-altered monzogranite and granodiorite. Some specimens are so strongly altered that the protholiths could not be clearly defined and were termed “hidrotermalitos”. All types are basically composed of alkali feldspar, quartz and plagioclase. The strong hydrothermal alteration produced an assemblage composed of chlorite, sericite, carbonate and opaque minerals. The opaque minerals are pyrite, sphalerite, pyrrhotite, chalcopyrite and galena, in decreasing amounts. Pb isotope composition of sulfide minerals was determined through the step leaching (two samples) and isotopic dilution (four samples) techniques. The step leaching results yielded isochronic ages of 2120±62 Ma (MSWD = 19) and 2242±290 Ma (MSWD = 34), whereas the isotopic dilution results produced an isochronic of 1978±43Ma (MSWD = 0,061). All ages are interpreted as reflecting the source of the Pb in the sulfides, which is consistent with the localization of the analytical points above the Pb growth curve. Model ages were calculated for all samples, according to the two-stage model, yielding ages between 1.86 Ga and 1.92 Ga. The age of 1.86 Ga is assumed as the nest approximation to the deposition age of the gold-sulfide ore is consistent with both Parauari and Maloquinha granitic events.